The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fgene.2020.01001
|View full text |Cite
|
Sign up to set email alerts
|

Breeding, Genetics, and Genomics Approaches for Improving Fusarium Wilt Resistance in Major Grain Legumes

Abstract: Fusarium wilt (FW) disease is the key constraint to grain legume production worldwide. The projected climate change is likely to exacerbate the current scenario. Of the various plant protection measures, genetic improvement of the disease resistance of crop cultivars remains the most economic, straightforward and environmental-friendly option to mitigate the risk. We begin with a brief recap of the classical genetic efforts that provided first insights into the genetic determinants controlling plant response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 259 publications
(344 reference statements)
1
15
0
Order By: Relevance
“…These results disclosed a grass pea oligogenic resistance to Fop race 2, corroborating the evidence of a quantitative nature of resistance revealed by the previous phenotypic characterization of this collection of accessions (Sampaio et al, 2021b). As revised by Sampaio et al (2020) and Jha et al (2020), an oligogenic resistance to fusarium wilt has been described in several other legumes. Examples are chickpea, for some races of Fo f. sp.…”
Section: Discussionsupporting
confidence: 88%
“…These results disclosed a grass pea oligogenic resistance to Fop race 2, corroborating the evidence of a quantitative nature of resistance revealed by the previous phenotypic characterization of this collection of accessions (Sampaio et al, 2021b). As revised by Sampaio et al (2020) and Jha et al (2020), an oligogenic resistance to fusarium wilt has been described in several other legumes. Examples are chickpea, for some races of Fo f. sp.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the experiments with both strains being conducted in few experiments under controlled conditions, some of the QTL identified in this study are confirmed by the literature, evidencing the robustness of results. However, the successful establishment of disease by the Fop pathogen demands a response in the plant defense system, and the entire molecular mechanism of pathogenesis remains to be elucidated to improve selective accuracy with additional experiments involving high-throughput phenotyping [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi show survival plasticity in most soil conditions, through the formation of thick-walled chlamydospores that can hibernate in the soil for years. This persistence is further enhanced through aggressive saprophytic mode in host plant debris and via released microconidia and macroconidia, which aid new infections and dispersal [ 60 , 66 ]. Therefore, a clear understanding of the disease cycle and mode of spread is required for the efficient implementation of diagnostic and control strategies.…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%